Making human papillomavirus testing a public health priority in Ecuador - Galárraga, Gustavo; López-Gil, José Francisco (Frontiers in Public Health, 2025)
Cervical cancer is a pressing public health issue in Ecuador, where it is the second most common cancer among women, with 1792 new cases and 939 deaths annually. Despite the availability of superior diagnostic methods like human papillomavirus deoxyribonucleic acid testing, the national strategy continues to prioritize Pap smears, limiting the effectiveness of early detection efforts. Disparities in screening access are evident, with only 54% of women aged 12–49 undergoing Pap smears, and coverage is even lower in marginalized populations. Learning from Peru’s National Cancer Law, Ecuador has the opportunity to adopt similar measures, ensuring free and equitable access to human papillomavirus (HPV) testing. By scaling up human papillomavirus screening, integrating vaccination programs, and addressing socioeconomic barriers, Ecuador can move closer to eliminating cervical cancer as a public health threat. The time to prioritize human papillomavirus testing is now.